Case report: First-in-human combined low-dose whole-heart irradiation and high-dose stereotactic arrhythmia radioablation for immunosuppressive refractory cardiac sarcoidosis and ventricular tachycardia - van der Ree, Martijn H.; Herrera Siklody, Claudia; Le Bloa, Mathieu; Pascale, Patrizio; Porretta, Alessandra P.; Teres, Cheryl C.; Solana Munoz, Jorge; Luca, Adrian; Domenichini, Giulia; Ozasahin, Mahmut; Jumeau, Raphael; Postema, Pieter G.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Cardiac sarcoidosis is associated with heart failure, conduction abnormalities and life-threatening arrhythmias including ventricular tachycardia. Radiotherapy has been suggested as treatment for extra-cardiac sarcoidosis in patients refractory to immunomodulatory treatment.The effectiveness and safety of low-dose whole-heart radiotherapy for therapy-refractory cardiac sarcoidosis was evaluated in a pre-post intervention case report comparing the 54 months before and after treatment. Immunomodulatory low-dose whole-heart irradiation as sarcoidosis treatment consisted of a 2x2 Gy scheme. Additionally, high-dose single fraction Stereotactic Arrhythmia Radioablation (STAR) of 1x20 Gy was applied to the pro-arrhythmic region to manage the ventricular tachycardia episodes. Cardiac sarcoidosis disease activity was measured by hypermetabolic areas on repeated [ 18 F]FDG-PET/CT scans and by evaluating changes in ventricular tachycardia episodes before and after treatment.One patient with therapy-refractory progressive cardiac sarcoidosis and recurrent ventricular tachycardia was treated. The cardiac sarcoidosis disease activity showed a durable regression of inflammatory disease activity from 3 months onwards. The [ 18 F]FDG-PET/CT scan at 54-months did not show any signs of active cardiac sarcoidosis and a state of remission was achieved. The number of sustained VT episodes was reduced by 95%. We observed the development of moderate aortic valve regurgitation likely irradiation-related. No other irradiation-related adverse events occurred and the left ventricular ejection fraction remained stable.We report here for the first time on the beneficial and lasting effects of combined immunomodulatory low-dose whole heart radiotherapy and high-dose Stereotactic Arrhythmia Radioablation in a patient with therapy-refractory cardiac sarcoidosis and recurrent VT.